The Correlation between Reading and Speaking Skills on Students’ English Learning as Foreign Language : Reading and Speaking Skills on Students’ English Learning as Foreign Language - Albadri Albadri; Noer Halimah (JOEY: Journal of English Ibrahimy, 2022)
Reading is the action of extracting meaning from a text or passage and obtaining information from the author. Speaking is the practice that using words to interact with others. Than English language learning is a behavior that tends to have relative provisions and produces strong actions. The problem that discussed are focused on reading and speaking skills because students felt unconfident to read and speak English and them afraid of making mistakes in English learning. This research used quantitative correlation design to approach the data. The population was 642 students’ at the first grade in SMA Ibrahimy sukorejo. The sample selected as many as 62 students in the study was carried out using a side-by-side purposive technique while data collection was carried out by tests and observations the data analysis used Pearson product moments to analyze the relationship between reading and speaking skills with learning English in class 1 socio IV at SMA Ibrahimy Sukorejo of Situbondo. The research's findings indicate that students' reading and speaking skills have a positive and correlation significant of English learning and alternative hypothesis is accepted. Based on The score sig 1.000 ≤ 0.05. The Alternative Hypothesis (Ha) is accepted based on the results of the hypothesis testing, and based on the output of the analysis of the Pearson formula in SPSS, it has a significant score (Sig) of 0.24 and 1.000. Score Sig 0.05 indicates that the independent variable has an impact on the dependent variable. It shows there is a correlation between reading and speaking skills in the first grade of social 4 at SMA Ibrahimy Sukorejo students learning English as a foreign language.